Turning a Nickelate Fermi Surface into a Cupratelike One through Heterostructuring - Hansmann, Philipp; Yang, Xiaoping; Toschi, Alessandro; Khaliullin, G.; Andersen, O. K.; Held, Karsten (Physical Review Letters, 2009)
Using the local density approximation and its combination with dynamical mean-field theory, we show that electronic correlations induce a single-sheet, cupratelike Fermi surface for hole-doped 1/1 LaNiO(3)/LaAlO(3) heterostructures, even though both e(g) orbitals contribute to it. The Ni 3d(3z)(2)-1 orbital plays the role of the axial Cu 4s-like orbital in the cuprates. These two results indicate that "orbital engineering" by means of heterostructuring should be possible. As we also find strong antiferromagnetic correlations, the low-energy electronic and spin excitations in nickelate heterostructures resemble those of high-temperature cuprate superconductors.
CRIS-Team WoS Importer:2020-02-19